Global foot-and-mouth disease research update and gap analysis: 1 – Overview of global status and research needs - Knight-Jones, Theodore J.D.; Robinson, L.; Charleston, B.; Rodríguez, L.L.; Gay, C.G.; Sumption, Keith J.; Vosloo, W. (Hindawi Limited, 2016)
The Global Foot-and-mouth disease (FMD) Research Alliance periodically reviews the state of FMD research to assess progress and to identify new priorities. In this supplement we provide an update of global FMD research, comprising (i) this overview paper, which includes background information with key findings, and papers covering (ii) epidemiology, wildlife and economics, (iii) vaccines, (iv) diagnostics, (v) biotherapeutics and disinfectants, (vi) immunology and (vii) pathogenesis and molecular biology. FMD research publications were reviewed (2011–2015) and activity updates were obtained from 33 FMD research institutes from around the world. Although a continual threat, FMD has been effectively controlled in much of the world using existing tools. However, control remains a challenge in most developing countries, where little has been done to understand the ongoing burden of FMD. More research is needed to support control in endemically infected countries, particularly robust field studies. Traditional FMD vaccines have several limitations including short duration and spectrum of protection, cold chain requirements, and the costs and biosecurity risks associated with vaccine production. Significant progress has been made in the development of novel vaccine candidates, particularly in the use of recombinant vaccines and virus-like particles as an alternative to traditional inactivated whole virus vaccines. Continued investment is needed to turn these developments into improved vaccines produced at scale. Increased knowledge of cellular and mucosal immunity would benefit vaccine development, as would further advances in our ability to enhance vaccine capsid stability. Developments in molecular biology and phylogenetics underlie many of the recent advances in FMD research, including improved vaccines and diagnostics, and improved understanding of FMD epidemiology. Tools for genetic analyses continue to become both more powerful and more affordable enabling them to be used to address an ever-expanding range of questions. This rapidly advancing field potentiates many areas of FMD research and should be prioritized.